Thai Consumers' Perceptions of Sustainable Food Packaging - Romprasert, Suppanunta; Srihachai, Atsanee; Tanamee, Danai; Wiriyapinit, Sutthanuch (Advances in Social Sciences Research Journal, 2024)
This study explored Thai consumers' perceptions of sustainable food packaging, investigating factors influencing their awareness, such as environmental consciousness and knowledge of eco-friendly options. Conducted through a structured survey with 800 Thai online food consumers, the research assessed attitudes toward plastic packaging waste, factors guiding the preference for sustainable options, and potential impacts on the food service industry. Findings revealed a substantial surge in Thai consumer interest in sustainable food packaging, driven by heightened environmental awareness. However, a significant gap emerged between consumer demand and the limited availability of sustainable options in the Thai online food sector. Despite growing interest, consumers lacked specific knowledge about diverse sustainable packaging alternatives and their environmental implications. This knowledge gap poses a challenge in aligning consumer aspirations with industry choices and the global sustainability standard such as ISO 14001, FDA guidelines and European Green Deal objectives. The study underscores the need for educational initiatives to enhance consumer awareness of clearing on eco-labeling to educate consumers on the sustainability benefits of the packaging. Bridging this knowledge gap is crucial to aligning consumer preferences with sustainability goals in the food packaging industry partnering with eco-certification bodies to enhance credibility. The research not only identifies trends but offers actionable steps for rising demand for sustainable alternatives, global regulatory push, and technology driven advancements. By implementing these recommendations, business as a leader in sustainability can meet market demands for sustainability, contributing to a more environmentally responsible future in the Thai online food industry regulatory requirements.